La tipificación del delito vientre de alquiler en el código orgánico integral penal - García Yagual, Carolina Pilar (2019)
The present study, entitled "THE CRIMINALIZATION OF CRIME 'BELLY IN RENT' IN THE PENAL ORGANIC INTEGRAL CODE", had the purpose of proposing the creation of a penal type where this practice is established. In this sense, according to the preventive function of criminal law, the incorporation of a numeral within article 91, regarding the different modalities of trafficking in persons, for the technique of assisted reproduction called 'Belly in rent', when it is perform for profit, either for the pregnant woman or for a third party, would help to prevent women, either by their will or coercion from a third party, agree to gestate a child for a mere commercial or economic gain……….